IMPLEMENTASI MODEL TGT (TEAMS GAMES TOURNAMENT) BERBASIS MEDIA WAYGROUND UNTUK MENINGKATKAN HASIL BELAJAR - Anggun Putri Pradani; Muhisom; Yoga Fernando Rizqi; Fadhilah Khairani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This investigation was prompted by the suboptimal attainment of Learning Objective Achievement Criteria (KKTP) in Pancasila Education among fifth-grade students at SD Negeri 5 Metro Timur. The study aimed to examine the effect of the Teams Games Tournament (TGT) cooperative learning model, integrated with Wayground media, on students' learning outcomes in Pancasila Education. A quantitative approach employing a quasi-experimental method with a non-equivalent control group design was utilized. The research sample comprised 44 students, with class VA designated as the control group and class VB as the experimental group. Data were collected through test and non-test instruments. Statistical analysis revealed a significance value of 0.000 < 0.05; consequently, H₀ was rejected and Hₐ was accepted. The findings indicate that the TGT cooperative learning model integrated with Wayground media exerted a significant effect on the learning outcomes of fifth-grade students in Pancasila Education at SD Negeri 5 Metro Timur